Hydroboration of Alkynes with Zwitterionic Ruthenium–Borate Complexes: Novel Vinylborane Complexes. Issue 32 (26th June 2015) - Anju, R. S.; Mondal, Bijan; Saha, Koushik; Panja, Subir; Varghese, Babu; Ghosh, Sundargopal
Abstract Building upon previous studies on the synthesis of bis(sigma)borate and agostic complexes of ruthenium, the chemistry of nido‐[(Cp*Ru)2B3H9] (1) with other ligand systems was explored. In this regard, mild thermolysis of nido‐1 with 2‐mercaptobenzothiazole (2‐mbzt), 2‐mercaptobenzoxazole (2‐mbzo) and 2‐mercaptobenzimidazole (2‐mbzi) ligands were performed which led to the isolation of bis(sigma)borate complexes [Cp*RuBH3L] (2 a–c) and β‐agostic complexes [Cp*RuBH2L2] (3 a–c; 2 a, 3 a: L=C7H4NS2; 2 b, 3 b: L=C7H4NSO; 2 c, 3 c: L=C7H5N2S). Further, the chemistry of these novel complexes towards various diphosphine ligands was investigated. Room temperature treatment of 3 a with [PPh2(CH2)nPPh2] (n=1–3) yielded [Cp*Ru(PPh2(CH2)nPPh2)‐BH2(L2)] (4 a–c; 4 a: n=1; 4 b: n=2; 4 c: n=3; L=C7H4NS2). Mild thermolysis of 2 a with [PPh2(CH2)nPPh2] (n=1–3) led to the isolation of [Cp*Ru(PPh2(CH2)nPPh2)(L)] (L=C7H4NS25 a–c; 5 a: n=1; 5 b: n=2; 5 c: n=3). Treatment of 4 a with terminal alkynes causes a hydroboration reaction to generate vinylborane complexes [Cp*Ru(RCCH2)BH(L2)] (6 and 7; 6: R=Ph; 7: R=COOCH3; L=C7H4NS2). Complexes 6 and 7 can also be viewed as η‐alkene complexes of ruthenium that feature a dative bond to the ruthenium centre from the vinylinic double bond. In addition, DFT computations were performed to shed light on the bonding and electronic structures of the new compounds.